Recent Study of Some Geotechnical Properties of White and Colored Kaolin Clay in Iraq Western Desert - Hamady, Ahmad Abed (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
During this research the geotechnical properties of Kaolin rocks white and colored has been studies. An experimental program was undertaken to study the effect of the presence of iron oxides (Fe2O3) on the geotechnical properties for the white and colored kaolin rocks. White Kaolin clay give the geotechnical properties more than the colored kaolin The iron oxide in colored kaolin destroyed the internal structure of the Kaolinitic mineral and decrease the crystallinity degree are decreasing and created porous because of influences of the oxidation. We can determine the (G dyne, K dyne, B, ?) parameters from (Vp, Vs) and we can determine (Easta) from (E dyne).The effect of compressive strength for white and colored kaolin show during: modulus Ratio, toughness modules) so that colored kaolin is weaker than white kaolin, because of effect of iron oxides on structure. The value of decreased resistance of white kaolin rocks higher rate than colored kaolin rocks.